Implementation of Local Product Marketing Strategy On Shop Kenanga In Regency Maros - Ayu Dilfasari Yasin; Andi Cudai Nur; Aris Baharuddin (Public Resource Innovation Management and Excellence, 2025)
Implementation of Local Product Marketing Strategies at Kenanga Stores in Maros Regency. Thesis for the Study Program of Business Administration, Faculty of Social Sciences and Law, Makassar State University. Supervised by Dr.H.Muhammad Guntur, M.Sc. and Dr. Andi Cudai Nur, M.Sc. This study aims to determine the marketing strategy for local products at Kenanga Stores in Maros Regency. This study used a qualitative method with a case study type based on the situation that occurred at Kenanga Store. Data collection was obtained from respondents in this study consisting of four people, namely shop owners, employees, and consumers from Kenanga Store. Data collection procedures used were observation, interviews, and documentation. The interview technique was carried out in a structured manner using interview guidelines. The results of the study show that Kenanga Store has implemented a marketing strategy for selling its local products, with a focus on three strategies, namely STP (Segmentation, Targeting, Positioning). The marketing strategy implemented by Toko Kenanga in this case is segmentation based on geographicand demographic variables. Targeting focuses on variable single-segment concentration (concentration on one segment). Positioning focuses on maintaining unique recipes, quality and affordable prices.